Penerapan Teknik Akrostik dalam Pembelajaran Menulis Puisi Pada Siswa Kelas XI Melati 1 SMA Negeri 4 Palembang - W, Widia; Mediana, Verga; Agustiani, Iis; H, Hetilaniar (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This study aims to improve poetry writing skills using acrostic techniques among students of class XI Melati 1 at SMA Negeri 4 Palembang. The research is descriptive qualitative in nature. It falls under the category of Class Action Research. The study was conducted in two cycles, with each cycle being implemented three times. The research procedure includes planning, implementing actions, observing, and reflecting. The subjects of this study were 34 students of class XI Melati 1 at SMA Negeri 4 Palembang. After conducting the research in the first cycle, 21 out of 34 students scored 72.35, qualifying as